The Antidepressant-Like Effects of Hesperidin in Streptozotocin‐Induced Diabetic Rats by Activating Nrf2/ARE/Glyoxalase 1 Pathway - Zhu, Xia; Liu, Haiyan; Liu, Yuan; Chen, Yajing; Liu, Yaowu; Yin, Xiaoxing (Frontiers in Pharmacology, 2020)
The co-occurrence of diabetes and depression is a challenging and underrecognized clinical problem. Alpha-carbonyl aldehydes and their detoxifying enzyme glyoxalase 1 (Glo-1) play vital roles in the pathogenesis of diabetic complications, including depression. Hesperidin, a naturally occurring flavanone glycoside, possesses numerous pharmacological properties, but neuroprotection by hesperidin in depression-like behaviours in diabetes was not observed. This study aimed to investigate the mechanisms and signalling pathways by which hesperidin regulates depression-like behaviours in diabetic rats and to identify potential targets of hesperidin. Rats with streptozotocin-induced diabetes were treated orally with hesperidin (50 and 150 mg/kg) or the nuclear factor erythroid 2-related factor 2 (Nrf2) inducer tert-butylhydroquinone (TBHQ, 25 mg/kg) for 10 weeks. After behavioural test, the brains were collected to evaluate the effects of hesperidin on Glo-1, Nrf2, protein glycation and oxidative stress. Hesperidin showed antidepressant and anxiolytic effects in diabetic rats, as evidenced by the decreased immobility time in the forced swimming test, increased time spent in the centre area of the open field test, and increased percentage of open-arm entries and time spent in the open arms in the elevated plus maze, as well as by the enhancement of Glo-1 and the inhibition of the AGEs/RAGE axis and oxidative stress in the brain. In addition, hesperidin caused significant increases in the Nrf2 levels and upregulated γ-glutamylcysteine synthetase, a well-known target gene of Nrf2/ARE signalling. In vitro, the effects of hesperidin on N2a cell injury caused by high glucose (HG) was assessed by MTT and LDH, and the effects on Nrf2 signaling were also assessed. We found that the Nrf2 inhibitor ML385 reversed the protective effects of hesperidin on the cell injury induced by HG. Hesperidin prevented the HG-induced reduction in the Nrf2 and Glo-1 levels, and ML385 reversed the effects of hesperidin on the expression of the proteins mentioned above, indicating that Nrf2 signalling is involved in the hesperidin-induced neuroprotective effects. Our findings indicate that the effects of hesperidin on ameliorating the depression- and anxiety-like behaviours of diabetic rats, which are mediated by the enhancement of Glo-1, may be due to the activation of the Nrf2/ARE pathway.